Emotionality and psychosexual maturity of male prison inmates - Małgorzata Anna Kuśpit; Martyna Nowak; Anna Tychmanowicz (Probacja, 2024)
Introduction. The aim of the presented analyzes is to determine the relationship between emotional intelligence and psychosexual maturity of men incarcerated in prisons. Materials and methods. The study involved 70 men incarcerated in prison, aged 21 to 64 (M=35.62), varied in terms of the length of the sentence and the possibility of applying for parole. The following research tools were used in the study: the Emotional Understanding Test (TRE, Matczak, Piekarska, 2011), the original Psychosexual Maturity Questionnaire (KPDP) in the experimental version and the Social Approval Questionnaire (KAS; Drwal, Wilczyńska, 1980) as a control scale. Results and conclusions. The results of the research indicate that the level of emotional intelligence of prisoners is usually average, and with its increase, the level of psychosexual maturity also increases. Statistical analyzes showed that there are no significant differences in emotional intelligence and psychosexual maturity between the group of first-time inmates and repeat offenders. The ability to apply for parole does not differentiate the level of emotional intelligence or psychosexual maturity. The obtained results also suggest a deficit of knowledge and competence in the field of psychosexual maturity from childhood. It is noticeable both in the case of first-time inmates, repeat offenders, men who can apply for parole and those who do not have such a possibility. Implications. Continuing research with prisoners and analyzing their psychosexual maturity, as well as various variables that may explain its level, may have many benefits, such as finding a way in which prisoners could fulfill their sexual needs or supplementing existing competences in the field of particular periods in the case of people who present average or high results.